2017
DOI: 10.1027/2151-2604/a000314
|View full text |Cite
|
Sign up to set email alerts
|

Young People’s Engagement With the European Union

Abstract: Abstract. This study investigated whether demographic variables, efficacy beliefs, visions, and worries are associated with four different forms of (dis)engagement with the European Union (EU): intended voting in the 2019 EU elections, nonconventional political engagement, psychological engagement, and the wish that one’s own country should leave the EU. The sample comprised 3,764 young people aged 16–25 years living in seven European countries: Albania, Austria, Germany, Italy, Romania, Spain, and the UK. Eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 14 publications
1
7
0
8
Order By: Relevance
“…The only finding to contradict the predictions of the uncertainty navigation model was the positive relationship between political engagement and worry, which suggests that becoming actively involved in steering the outcome of the election failed to reassure these engaged voters. Of course, this finding is consistent with the study mentioned earlier that examined worry in the context of issues relevant to the European Union (Strohmeier et al, 2017). The authors of that study posited that worry leads to engagement, rather than the other way around-a plausible explanation for our finding as well.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The only finding to contradict the predictions of the uncertainty navigation model was the positive relationship between political engagement and worry, which suggests that becoming actively involved in steering the outcome of the election failed to reassure these engaged voters. Of course, this finding is consistent with the study mentioned earlier that examined worry in the context of issues relevant to the European Union (Strohmeier et al, 2017). The authors of that study posited that worry leads to engagement, rather than the other way around-a plausible explanation for our finding as well.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have identified a negative relationship between control and worry in the context of academic pursuits (Putwain, Woods & Symes, 2010) and medical tests (Dawson, Savitsky, & Dunning, 2006), and other work has linked general perceptions of control to lower overall worry (Chapman, Kertz, & Woodruff-Borden, 2009;Zebb & Beck, 1998). In contrast, and most relevant to the current investigation, greater political engagement (one marker of perceived control over political outcomes) was associated with greater politically-relevant worry in a study of attitudes and engagement with issues relevant to the European Union (Strohmeier et al, 2017). However, in that study, the authors interpreted the relationship as suggesting that more worried participants were more motivated toward engagement, rather than the other way around (i.e., engagement predicting worry).…”
Section: Risk Of Receiving Bad Newsmentioning
confidence: 59%
“…Se utilizó una batería de instrumentos que ha sido validada en estudios previos con la muestra de referencia; con ella se evaluaban las siguientes variables: -Información demográfica: preguntas abiertas relativas al género, edad, país de nacimiento, nacionalidad, país de residencia, país de nacimiento de la madre, país de nacimiento del padre, estado civil, ocupación actual y nivel académico. -Prioridades con respecto al futuro (Strohmeier et al, 2017):…”
Section: Instrumentosunclassified
“…se utilizó una escala compuesta por 19 ítems que pedía a los y las participantes que indicaran las cuestiones que consideraban más importantes, con un formato de respuesta de 5 puntos (1 = en absoluto; 5 = mucho) (a = .78). -Preocupaciones con respecto al futuro de Europa (Strohmeier et al, 2017): se utilizó una escala compuesta por 31 ítems que pedía a los y las participantes que indicaran las cuestiones que consideraban más importantes, con un formato de respuesta de 5 puntos (1 = en absoluto; 5 = mucho) (a = .93). -Visiones sobre el futuro de Europa (Strohmeier et al, 2017): se utilizó una escala compuesta por 39 ítems, que pedía a los y las participantes que indicaran las cuestiones que consideraban más importantes, con un formato de respuesta de 5 puntos (1 = nada importante; 5 = muy importante) (a = .94).…”
Section: Instrumentosunclassified
See 1 more Smart Citation